Production of chitinolytic enzymes with Trichoderma longibrachiatum IMI 92027 in solid substrate fermentation - Krisztina Kovacs; Gyorgy Szakacs; Tunde Pusztahelyi; Ashok Pandey (浙江大学学报. 农业与生命科学版)
Thirty Trichoderma strains representing 15 species within the genus have been screened for extracellular production of chitinolytic enzymes in solid substrate fermentation (SSF). T. longibrachiatum IMI 92027 (=ATCC 36838) gave the highest yield (5.0 IU/g dry matter of substrate) after 3 days of fermentation on wheat bran-crude chitin (9:1 mixture) medium. The optimum moisture content (66.7%), chitin content (20%), initial pH of the medium (2-5) and time course (5 d) of SSF were determined for strain IMI 92027. No significant effect of different N and P additives was found on the chitinase yield in wheat bran-chitin mixture medium.Cellulase, xylanase, alpha-amylase and beta-xylosidase activities were also detected. The pH and temperature optima of chitinase complex of T. longibrachiatum IMI 92027 was found to be at 4.5 and 55 ℃, respectively. The enzyme totally lost its activity at 70 in 5 min in the absence of the substrate but retained about 15% of its initial activity even at 70 ℃ after incubation of 60 min in the presence of SSF solids (residual substrate and fungal mycelium).Purification of protein extract from the SSF material revealed high chitinolytic activities between pI 5.9-4.8 where N-acetyl-β-D-hexosaminidase and chitinase peaks have been found in the same pI range. Chitinase peaks could be described at least at four pI values: pI 5.9; 5.6; 5.3 and 4.8 while at least four main N-acetyl-β-D-hexosaminidase peaks could be separated at pI 6.0 and 5.1 and at more basic isoelectric points of 7.2 and 8.0. Two chitinases with 43.5 kDa and 30 kDa were purified at acidic isoelectric point.